2014
DOI: 10.1007/s00330-014-3201-2
|View full text |Cite
|
Sign up to set email alerts
|

The value of diffusion-weighted imaging in the detection of prostate cancer: a meta-analysis

Abstract: ObjectivesTo evaluate the diagnostic performance of diffusion-weighted imaging (DWI) as a single non-invasive method in detecting prostate cancer (PCa) and to deduce its clinical utility.MethodsA systematic literature search was performed to identify relevant original studies. Quality of included studies was assessed by QUADAS-2 (Quality Assessment of Diagnostic Accuracy Studies). Data were extracted to calculate sensitivity and specificity as well as running the test of heterogeneity and threshold effect. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 77 publications
4
41
3
2
Order By: Relevance
“…This technique allows the integration of anatomical, biological and functional information. Most studies using histopathology specimens as reference standards have shown that mpMRI outperforms conventional anatomical imaging alone for the detection of prostate cancer [33][34][35][36]. There is also evidence that unfavorable findings on mpMRI, especially low ADC values, are associated with adverse histological features [37,38].…”
Section: Mri In Active Surveillancementioning
confidence: 99%
“…This technique allows the integration of anatomical, biological and functional information. Most studies using histopathology specimens as reference standards have shown that mpMRI outperforms conventional anatomical imaging alone for the detection of prostate cancer [33][34][35][36]. There is also evidence that unfavorable findings on mpMRI, especially low ADC values, are associated with adverse histological features [37,38].…”
Section: Mri In Active Surveillancementioning
confidence: 99%
“…The sensitivity and specificity of DWI alone for the detection of carcinoma of the prostate are specified in a current meta-analysis including a total of 1204 patients as 62 % and 90 %, respectively [24]. In a meta-analysis including a total of 698 patients with a previous negative prostate biopsy, the average sensitivity of DWI for detecting a carcinoma of the prostate is 38 % and the average specificity is 95 % [25].…”
Section: Dwi Dce-mri 1 H-mrsmentioning
confidence: 99%
“…This may be due to the low positive predictive value of PSA, which accounts for a high proportion of unnecessary biopsies [4][5][6] . However, the negative predictive value (NPV) of TRUS-guided biopsy has been reported as between 36% and 89% [7] , with some patients being intolerant of this invasive procedure [8] . Where a negative biopsy is associated with continued suspicious clinical symptoms (continued rising PSA > 4.0 ng/mL, suspicious digital rectal examination, abnormal PSA velocity), repeat biopsies pose an even greater risk of negative rate for cancer detection than the initial biopsy (81%-83%) [9] , with second, third, and fourth re-biopsies detecting cancer in only 25% to 27%, 5% to 24%, and 4% to 21% of cases, respectively [10] .…”
Section: Traditional Biopsy In Prostate Cancermentioning
confidence: 99%
“…Ultimately, the motion of water molecules is more restricted in tissues with high cellular density associated with numerous intact cell membranes, such as tumour tissue [20] . This decrease in water diffusion has been attributed to the increased cellularity of the malignant tumour, with a reduction of the extracellular space and restriction of the motion of extracellular water [8] .…”
Section: Diffusion-weighted Mri (Dw-mri) In Prostate Cancer Diagnosismentioning
confidence: 99%
See 1 more Smart Citation